Dampak Penerapan IFRS pada Nilai Perusahaan (Book Value) Jakarta Islamic Index - Muhammad Titan Terzaghi (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2017)
Financial Statements Information is an important information for financial reports users. Investors want financial statements have transparency and can be compared between the companies at worldwide. One feature of transparency is the amount of the disclosure. The disclosure will reduce asymmetric information between investors and management, which will ultimately on reducing the risk faced by investors. IFRS differences is a solution for better standards globally oriented so that the IFRS is applied to bring good impact for company. This research wanted to know the impact of IFRS implementation in Indonesia against corporate value and relevance of accounting information value. The sample used by this research was companies listed at the Jakarta Islamic Index. Results found that the differences of Book Value before and after IFRS. But the relevance information value after IFRS is smaller than before IFRS.